2004
DOI: 10.1070/rc2004v073n02abeh000837
|View full text |Cite
|
Sign up to set email alerts
|

Self-propagating high-temperature synthesis of nanomaterials

Abstract: The results of recent studies in the field of self-propagat-The results of recent studies in the field of self-propagating high-temperature synthesis of nanosized materials are sur-ing high-temperature synthesis of nanosized materials are surveyed. The possibilities of the synthesis of nanomaterials in the veyed. The possibilities of the synthesis of nanomaterials in the combustion mode are demonstrated. Examples of applications of combustion mode are demonstrated. Examples of applications of the self-propagat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 44 publications
1
28
0
2
Order By: Relevance
“…a b During SHS of porous titanium nickelide, glowing of different intensity was repeatedly observed in the local regions of the reaction zone. These observations suggest thermal heterogeneity of the reaction zone and this corresponds to the experimental results obtained in the study of different SHS systems reported by other authors [8][9][10]. They showed that the heat released during the reaction in SHS is distributed as self-similar traveling waves, and the reaction front has a fractal structure.…”
Section: Resultssupporting
confidence: 66%
“…a b During SHS of porous titanium nickelide, glowing of different intensity was repeatedly observed in the local regions of the reaction zone. These observations suggest thermal heterogeneity of the reaction zone and this corresponds to the experimental results obtained in the study of different SHS systems reported by other authors [8][9][10]. They showed that the heat released during the reaction in SHS is distributed as self-similar traveling waves, and the reaction front has a fractal structure.…”
Section: Resultssupporting
confidence: 66%
“…As it follows from the review [24], such products cannot be obtained in composite systems by means of conventional SHS.…”
Section: Resultsmentioning
confidence: 97%
“…In all examined multicomponent SHS systems, the size of ceramic-phase particles substantially decreases as the content of the inert matrix in the reactive mixture increases. In the conventional SHS, however, it is hardly possible to obtain ceramicphase particles smaller than 1 µm [24].…”
Section: Introductionmentioning
confidence: 98%
“…The particle size of the ceramic phase is found to decrease substantially with increasing content of the inert matrix in the reactive mixture in all examined multispecies SHS systems. Nevertheless, the conventional SHS methods usually cannot ensure obtaining ceramic particles smaller than 1 µm [7,8].…”
Section: Introductionmentioning
confidence: 99%